# If y-3=7 and x+3y=6 then x=?Show your work.

*print*Print*list*Cite

### 8 Answers

I can't answer x+3y=6 right now. I have two variables (x and Y) so I'm stuck.

So, I turn to my other equation. y-3=7. If I add three to each side of the equation, I get y=10.

Now that I know y=10, I can put the number 10 in every place there was a "y." So, the second equation looks like this...

x+3y=6

x+3(10)=6

x+30=6 So I subtract 30 from each side.

x=-24

I then check myself by putting all my numbers back into the original equations.

10-3=7 and -24+3(10)=6

Yep, that works.

y-3=7-----(i)

x+3y=6----(ii)

x=?

In order to find the value of x we must first find the value of y, to do that let us first consider equation (i): y-3=7

y-3=7-----(i)

y-3+3=7+3 (adding 3 on both sides)

**y=10**

Then, we input the value of y in equation (ii): x+3y=6

x+3y=6

Input the value of y in this equation i.e 10

x+3(10)=6

x+30-30=6-30 (subtract 30 from both sides)

**x= -24 Answer.**

If y-3=7 and x+3y=6 then x=?

First let's find what " y " equals

**y - 3 = 7 **add 3 on both sides

By adding, you should get

**y = 10 **which is what " y " equals

Now plug 10 into the equation

**x + 3 ( 10 ) = 6 **multiply 3 with 10

By multiplying, you should get

**x + 30 = 6 **now subtract 30 on both sides

By subtracting, your equation should look like

**x = -24 **which Is your answer

If y-3=7 and x+3y=6 then x=

we need ot get the unkown variables by themselves, and usually you start with the equation that only has one unknown variable, wheich would be y-3=7

you add three to both sides so the -3 goes away leaving you with the value of y

y=10

then you plug this value into the other equation x+3y=6

to give you X+ 3(10) = 6

X+30=6

then you do the same thing, you try to get the 30 onto the right side by subtracting 30 from both sides so it gives you the value of X

X= -24

y-3=7 and x+3y=6 then x=

y - 3 = 7

+3 +3

y=10

plug in the number in the second problem

x+3(10)=6

x+30=6

-30 -30

x= -24

If y-3=7 and x+3y=6 then x=?

First solve for y because we have enough information for that.

y = 3 + 7 = 10

plug into the other equation:

x + 3(10) = 6

x + 30 = 6

x = 6 - 30 = -24

y-3=7

y-3+3=7+3

y=10

x+3y=6

x+3(10)=6

x+30=6

x+30-30=6-30

x=-24

Well

x+3y=6 and y-3=7

(+3)y-3=7(+3)

y=10

x+3(10)=6

x+30=6

x= -24